2006
DOI: 10.1074/jbc.m513717200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Efficient Processing and Activation of Recombinant Human UDP-N-acetylglucosamine:Lysosomal-enzyme-N-acetylglucosamine-1-phosphotransferase

Abstract: Mannose 6-phosphate-modified N-glycans are the determinant for intracellular targeting of newly synthesized lysosomal hydrolases to the lysosome. The enzyme responsible for the initial step in the synthesis of mannose 6-phosphate is UDP-N-acetylglucosamine:lysosomalenzyme-N-acetylglucosmine-1-phosphotransferase(GlcNAc-phosphotransferase). GlcNAc-phosphotransferase is a multisubunit enzyme with an ␣ 2 ␤ 2 ␥ 2 arrangement that requires a detergent for solubilization. Recent cloning of cDNAs and genes encoding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…The above two mutations consequently lead to frameshift. The Korean group reported skipping of exon 13 only in ML III g (1) g (6) g (6) g (2) g 4 3…”
Section: -------------------------40651 26408-------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…The above two mutations consequently lead to frameshift. The Korean group reported skipping of exon 13 only in ML III g (1) g (6) g (6) g (2) g 4 3…”
Section: -------------------------40651 26408-------------------mentioning
confidence: 99%
“…The a-b boundary is located within exon 14, but the detailed mechanism of processing the precursor into a and b subunits is not clear. 6 A series of genetic-complementation studies have shown heterogeneity in ML III and the genetic relationship between ML II and III. [7][8][9] Mutations in GNPTAB cause both the severe type of ML (ML II alpha/beta, ML II, I-cell disease (MIM 252500)) and the attenuated type of ML (ML III alpha/beta, ML IIIA, PseudoHurler polydystrophy (MIM 252600)).…”
Section: Introductionmentioning
confidence: 99%
“…The GNPTAB gene encodes the ␣ and ␤ subunits, whereas the GNPTG gene encodes the ␥ subunit. Enzyme kinetic studies have indicated that the ␣ and ␤ subunits specifically bind lysosomal acid hydrolases and mediate the catalytic function of the enzyme (8,9). The ␥ subunit enhances the rate of GlcNAc-P transfer to a subset of the acid hydrolases without substantially altering the binding to these acceptors.…”
mentioning
confidence: 99%
“…The ␣/␤ subunits contain three identifiable domains as follows: the Stealth domain, two Notch repeat modules, and a DNA methyltransferase-associated protein (DMAP) interaction domain. The Stealth domain resembles sequences within bacterial genes that encode sugar-phosphate transferases involved in cell wall polysaccharide synthesis and has been shown to mediate the catalytic function of GlcNAc-1-phosphotransferase (8,10,11). Importantly, the bacterial genes lack the Notch repeats and the DMAP interaction domain, which has been proposed to function as a protein-protein interaction domain (12).…”
mentioning
confidence: 99%
“…Most lysosomal enzymes including αliduronidase require an M6P tag for efficient uptake/lysosomal delivery in human cells. We investigated whether the phosphorylation of Nglycan terminal mannose residues of the 'test' αliduronidase could be achieved in vitro using recombinant soluble UDP-GlcNAc:lysosomal enzyme Nacetylglucosamine1phosphotransferase 21 (Fig. 6b).…”
Section: Strategy For Expression Of Human α-L-iduronidase In Maizementioning
confidence: 99%